The criticality of FDI in environmental degradation through financial development and economic growth: implications for promoting the green sector - Muhammad Qamri, Ghulam; Sheng, Bin; Muhammad Adeel-Farooq, Rana; Alam, Gazi Mahabubul (Elsevier, 2022)
The indirect role of foreign direct investment in environmental degradation has received little attention, and perhaps no study has yet shown the mediating role of financial development and economic growth in mediating the relationship between foreign direct investment and environmental degradation, especially in Asian economies, using panel data approaches for 21 Asian countries over the period of 1980–2018. Our findings show that foreign direct investment has a considerable positive impact on environmental quality through reducing pollutant levels. Economic growth is boosted greatly by foreign direct investment. Foreign direct investment, on the other hand, has a major negative impact on economic growth and financial development. Finally, both financial development and economic growth significantly negatively influence environmental degradation. According to the results of our study, in order to boost economic development and environmental quality, authorities should focus on the inflow of foreign direct investment. It is strongly recommended that policymakers reduce political involvement (Political stability) in the inflow of foreign direct investment, so that financial resources can be dispersed evenly in the industrial sector and nations can achieve a clean environment. Economic growth and financial development have been highlighted as mechanisms through which foreign direct investment influences carbon emissions. To enhance environmental sustainability, our study suggests that foreign direct investment be prioritized alongside investments in financial development.